The Republic of Ghana : Selected Policy Issues - World Bank (Washington, DC, 2012)
Following the December 2010 start-up of the Jubilee Field, Ghana has begun receiving royalty and tax revenues from oil production. At peak production, Jubilee could generate over US$1 billion in annual revenues for Ghana, a figure that will constitute 3 percent of 2011 non-oil Gross Domestic Product, or GDP and 18 percent of total government revenue. Recognizing the critical role oil revenues will play in Ghana's economic development; government is increasingly focused on generating short-term and long-term forecasts of oil revenues as inputs to its planning and policy-making. Oil revenue forecasts are needed for budgeting, long-term and medium-term fiscal planning, tax policy, and a broad set of petroleum and energy sector policy decisions. The immediate focus is on predicting the revenues that will flow from Jubilee itself; however, the announcements of significant additional discoveries at Mahogany Deep, Enyenra, Tweneboa, Teak, Sankofa, Dzata, and Paradise suggest that long-term oil revenues could be derived from multiple sources. Oil revenue forecasting is not intrinsically difficult but attention to details is important. For Ghana, the most challenging implementation details will be the ones related to the start-up of oil production at Jubilee. Price volatility is an ever-present challenge to forecasters but there are accepted approaches for taking this into account. However, the key to a successful on-going revenue forecasting process is to develop defined responsibilities and routines for information sharing, consistent and realistic methods for forecast calculation, and clear communication and dissemination of assumptions and results.